How SoTL-active faculty members can be cosmopolitan assets to an institution - Bernstein, Daniel (Teaching and Learning Inquiry, 2013)
Faculty members engaged in the Scholarship of Teaching and Learning generate visible analyses of the learning taking place in their institutions, provide excellent models of practice for local colleagues, generate high-quality evidence for internal and external assessment, and offer accessible examples of quality education to prospective students. SoTL contributions of this kind should be nurtured by institutions as a basic expectation of high-quality instruction. I discuss these faculty contributions as assets derived from a cosmopolitan social role within their organizations, and I develop a recommendation for institutional strategy from that perspective.